A Comparative Evaluation of Induction Characteristics of Propofol with Fentanyl and Ketamine as Total Intravenous Anaesthesia - Roseline Zohra Ali; Sanjeev Kumar Agrawal; Priyadershini Rangari (Academia Anesthesiologica International, 2020)
Background: Total intravenous anaesthesia has gained popularity, partly in order to reduce pollution by volatile agents. Propofol has proven to be suitable as a hypnotic for TIVA. The drug has fast onset of action and rapid metabolismwithout accumulation.Objectives:To compare propofol in combination with ketamine and fentanyl in TIV A technique in a population of Chhattisgarh region.Subjects and Methods: Patients of group-I were induced with ketamine andpropofol.Patients of group-II were induced with fentanyl and propofol. Parameters like Induction time, induction dose and total dose of propofol, top up doses of ketamine and fentanyl were observed and recorded. Continuous monitoring of pulse rate, arterial blood pressure, respiratory rate and arterial oxygen saturation was done throughout peri-operative period and readings were recorded at different time interval.Results: Propofol and ketamine combination took less time. The induction dose and total dose of propofol was less in propofol ketamine as compared to in propofo1 fcntany1 group. Number of top-ups of ketamine were less than the number of top ups of fentanyl. Stability of pulse and blood pressure with propofol ketamine combination were comparable and better.In propofol ketamine group respiratory rate was wellmaintained within normal range.Maintenance of arterial oxygen saturation was good with both the groups. Propofol ketamine combination took longer time for recovery from anaesthesia in comparison with propofol fentanyl combination. Conclusion: So to conclude, combination of propofol and ketamine gives better haemodynamic stability during induction and maintenance of total intravenous anaesthesia. Sub anesthetic doses of ketamine may be an alternative, cheaper analgesic to supplement propofol anaesthesia, instead of short acting potent expensive opioids like fentanyl.